The formation of stable hydrogen impermeable TiN-based coatings on zirconium alloy Zr1%Nb - Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Tyurin Yu. I. Yuri Ivanovich; Syrtanov M. S. Maksim Sergeevich; Zhang Le (2015, 2015)
Title screen